Stability Analysis of a Modified Leslie–Gower Predation Model With Weak Allee Effect in the Prey - Arancibia-Ibarra, Claudio; Flores, José D.; van Heijster, Peter (Frontiers in Applied Mathematics and Statistics, 2022)
In this manuscript, we study a Leslie-Gower predator-prey model with a hyperbolic functional response and weak Allee effect on the prey. The results reveal that the model supports coexistence and oscillation of both predator and prey populations. We also identify regions in the parameter space in which different kinds of bifurcations, such as saddle-node bifurcations, Hopf bifurcations and Bogdanov-Takens bifurcations, take place.